Evaluation of the Performance of Summer Tomato Lines in Bangladesh Conditions - Das, Saurav Brata; Islam, Md Shahidul; Uddin, M Nazim; Goswami, Bani Krishna; Abedin, S M Shafiul; Baki, Md Abdul (Journal of Bio-Science, 2024)
The experiment was carried out at the Olericulture division of the Bangladesh Agricultural Research Institute's experimental field in Joydebpur, Gazipur. The objective was to evaluate the performance of eleven potential inbreed lines (CLN-3849, CLN-3850, CLN-3859, CLN-3860, CLN-3862, CLN-3864, CLN-3906, CLN-3916, CLN-3735, CLN-3791, CLN-3792) along with BARI Hybrid Tomato-8. Data on different parameters such as, plant height (cm), days to 50% flowering, individual fruit weight, fruit length, fruit breadth, locules number per fruit, Total Soluble Solids (TSS), pericarp thickness (cm), number of fruits per plant and fruit yield per plant were measured. Significant differences were observed in terms of plant height, days to 50% flowering, single fruit weight, number of locules and pericarp thickness among the genotypes. The outcome showed that the 12 tomato genotypes varied in the quantity of fruits produced per plant. Number of fruits per plant of different tomato line ranged from 7.33 to 21.67. It was found that the genotype BARI Hybrid Tomato-8 had maximum number of fruits per plant (21.67) followed by CLN-3791 (18.33) whereas the inbred line CLN-3791 produced maximum quantity of fruits (1.616 kg/plant). J. Bio-Sci. 31(2): 13-23, 2023